An approach for accuracy enhancement of five-axis machine tools based on quantitative interval sensitivity analysis. (June 2020) - Fan, Jinwei; Tao, Haohao; Pan, Ri; Chen, Dongju
Highlights: The influence mechanism of geometric errors on the form errors of S-shaped test piece is investigated. The quantitative interval sensitivity analysis method for identifying key geometric errors at different intervals is proposed. The compensation for the identified key geometric errors is conducted and verified by the simulation and experiment. Abstract: Error compensation is a common method to improve the machining accuracy of five-axis machine tools (FAMTs). Before that, in order to identify the key geometric errors that affect the machining accuracy, sensitivity analysis (SA) in entire machining region or a specified point is usually used. However, since the influence of geometric errors on form errors is different in each interval, the result of SA would be affected, which decreases the compensating accuracy. For this reason, a new approach for accuracy enhancement of FAMTs based on quantitative interval sensitivity analysis (QISA) is presented in this paper. First, based on multi-body system theory and homogeneous transform matrix, the volumetric error model of the FAMT is established. Then, the geometric error model of the FAMT is formulated. Second, development of form error model is involved in this paper to clarify the effect law of geometric error on form error. Moreover, the machining region of S-shaped test piece is divided into five intervals. Then, the QISA method is presented to calculate the sensitivity index of each geometric error and identify key geometric errors at different intervals. Finally, simulations and experiments are conducted to validate the feasibility and effectiveness of the presented method.